Menanam Cabai, Menanam Harapan : Strategi Masyarakat dalam Mewujudkan Ketahanan Pangan di Lingkungan Pelabuhan Pelindo Jayapura: Pengabdian - Ika Fitrianita (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
This community service program, through the Movement for Planting Vegetables, aims to strengthen household and community food security by utilizing home gardens and limited land in the Pelabuhan Pelindo Petikemas Jayapura area. The methods included socialization, chili cultivation training, assistance, and regular monitoring. The results indicate an increase in community knowledge and skills in chili cultivation, leading to greater household availability of chili and reduced household expenditure. Some households also gained additional income by selling surplus harvests. Socially, this activity fostered collective awareness of the importance of food self-sufficiency and strengthened community solidarity. Therefore, the chili planting movement can serve as an effective strategy to enhance food security while improving community welfare sustainably.